2006
DOI: 10.1161/circulationaha.105.606145
|View full text |Cite
|
Sign up to set email alerts
|

Familial Sudden Death Is an Important Risk Factor for Primary Ventricular Fibrillation

Abstract: Background-Primary ventricular fibrillation (VF) accounts for the majority of deaths during the acute phase of myocardial infarction. Identification of patients at risk for primary VF remains very poor. Methods and Results-We performed a case-control study in patients with a first ST-elevation myocardial infarction (STEMI) to identify independent risk factors for primary VF. A total of 330 primary VF survivors (cases) and 372 controls were included; patients with earlier infarcts or signs of structural heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
160
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(175 citation statements)
references
References 21 publications
8
160
1
6
Order By: Relevance
“…34 Several studies have also demonstrated a familial predisposition to SCD that may or may not be related to genetic channelopathies. [35][36][37] Coronary spasm is also a cause of cardiac arrest, particularly in male smokers with minimal or no pre-existing CAD. 38 Mitral valve prolapse in female patients with ECG repolarisation abnormalities, and frequent complex ventricular ectopy, has also been associated with out-of-hospital cardiac arrest.…”
Section: Department Of Defense Cardiovascular Death Registry In the Umentioning
confidence: 99%
“…34 Several studies have also demonstrated a familial predisposition to SCD that may or may not be related to genetic channelopathies. [35][36][37] Coronary spasm is also a cause of cardiac arrest, particularly in male smokers with minimal or no pre-existing CAD. 38 Mitral valve prolapse in female patients with ECG repolarisation abnormalities, and frequent complex ventricular ectopy, has also been associated with out-of-hospital cardiac arrest.…”
Section: Department Of Defense Cardiovascular Death Registry In the Umentioning
confidence: 99%
“…Furthermore, patients with similar risk factors for CAD may suffer from SCD or nonfatal ischemic events. Although the explanation for this difference is far from clear, data from a recent case-control strongly suggest that there is a genetic predisposition to primary VF in the setting of an acute MI [49]. Furthermore, there is new understanding of the cascade that relates the distal events of atherosclerosis to the proximal event of SCD.…”
Section: Atherosclerosis and Thrombosis Cascadementioning
confidence: 99%
“…4 Genetic susceptibility to SCD in the setting of CAD is supported by several epidemiologic studies demonstrating that a family history of SCD is an independent risk factor for SCD and primary VF. 5,6,7 Sympathetic activation, mediated by the β adrenergic receptors β1AR and β2AR, favors the development of ventricular arrhythmias (VA) and SCD. 2,[8][9][10][11][12] Two common nonsynonymous single nucleotide polymorphisms (SNPs) in each of the single-exon β1AR and β2AR genes are observed: β1AR Ser49Gly and Arg389Gly, and β2AR Gly16Arg and Gln27Glu, the latter two of which are in linkage disequilibrium (LD).…”
Section: Introductionmentioning
confidence: 99%